Advance tunnel alert system / Mohd Shamian Zainal and Danial Md Nor - Zainal, Mohd Shamian; Md Nor, Danial (2006)
This project is to design and fabricate an alarm system for tunnel application by using a PIC16F877 as the central controlling unit. The purpose of the alarm system is to save human live in case of tunnel collapsing. The system is designed to detect any angle changes at the walls of tunnels, and give an early warning of the happening of failure of tunnel. It has done with the application of angle sensors that are able to sense the changing of angles of walls.